Effect of protein sources on growth, survival, feed conversion and protein utilization in fry of red tilapia (Oreochromis niloticus) - Neethiselvan, N; Manikandavelu, D; Jasmine, G Indra; Venkataramani, V K (Indian Journal of Fisheries, 2011)
Feeding experiment conducted to determine the protein requirement of redtilapia (Oreochromis niloticus) revealed a significantly (P0.01) from those fed with 35% protein.However, the feed conversion efficiency and protein efficiency ratio of the animalsfed with 35 and 40% protein diet varied significantly (P